Qur’an Memorisation Using the Master Method and the Yadain Method (A Comparative Study at Ma’had Askar Kauny Istiqomah in Bergas, Semarang, and Pondok Pesantren Miftahul Huda in Siwatu, Wonosobo) - Imam Fakhrurrozi; Abdul Khamid; Mushbihah Rodliyatun (CV. Creative Tugu Pena, 2026)
Each Islamic boarding school has its own way or method of memorizing the Qur'an in order to produce a qualified tahfidz. This study aims to find out how to memorize the 30 juz of the Qur'an as easily as possible so that people do not feel burdened and have a positive thinking power to always be enthusiastic in memorizing. This study uses qualitative research, which aims to describe the empirical reality behind a phenomenon in depth, detail, thoroughly and systematically. The data collected in qualitative research are not in the form of numbers, but data derived from observations, interview scripts, field notes, personal documents, and other official documents. This master method was discovered by Ustadz H. Bobby Herwibowo, Lc in 2011 and the concept used for memorizing is by utilizing all five senses, there are three factors that dominate this concept, namely: audio, namely with a loud voice, visual by seeing existing movements or images and kinesthetic, namely with hand or head movements that show the meaning of what is read. When applied to memorizing the Qur'an, these three factors will make it easier for the individual. The Yadain method, developed by Yadi Iryadi, S.Pd., and Saied Al-Makhtum, utilizes the visual concepts of tadabbur (recitation), the Qur'an, and the finger of the Qur'an. The conclusion is that the Master and Yadain methods are effective for memorizing the 30 chapters of the Qur'an for all Muslims.